2022
DOI: 10.1038/s41467-022-31416-y
|View full text |Cite
|
Sign up to set email alerts
|

A-site cation influence on the conduction band of lead bromide perovskites

Abstract: Hot carrier solar cells hold promise for exceeding the Shockley-Queisser limit. Slow hot carrier cooling is one of the most intriguing properties of lead halide perovskites and distinguishes this class of materials from competing materials used in solar cells. Here we use the element selectivity of high-resolution X-ray spectroscopy and density functional theory to uncover a previously hidden feature in the conduction band states, the σ-π energy splitting, and find that it is strongly influenced by the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 61 publications
(67 reference statements)
4
18
0
Order By: Relevance
“…This is also seen in the peak at 9.7 eV. Close inspection of the three prominent conduction band peaks from 1 to −3 eV shows that p x and p y , representing π interactions, and the p z σ bond all contribute equally to the first peak, while the second and third peaks are predominantly from I p z sigma bonds, in agreement with previous research on the conduction band of bromide HOIPs . Moreover, the I p z levels match reasonably closely the lead levels in the valence band edge because of the σ character, while the p x and p y levels with their out-of-plane π character do not.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is also seen in the peak at 9.7 eV. Close inspection of the three prominent conduction band peaks from 1 to −3 eV shows that p x and p y , representing π interactions, and the p z σ bond all contribute equally to the first peak, while the second and third peaks are predominantly from I p z sigma bonds, in agreement with previous research on the conduction band of bromide HOIPs . Moreover, the I p z levels match reasonably closely the lead levels in the valence band edge because of the σ character, while the p x and p y levels with their out-of-plane π character do not.…”
Section: Resultssupporting
confidence: 88%
“…In both MAPI and MAI materials, the MA + ions can interact with the iodide ions, but MAPI additionally has an inorganic PbI 3 – framework, which is sensitive to the organic cations . In a recent study, we have shown that the valence and conduction bands of lead bromide perovskites (APbBr 3 ) are strongly influenced by interactions with the positive cations at the A-site …”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bonding yields a slight nitrogen admixture in the upper valence band, which recently has been discussed in the context of nitrogen K-edge X-ray emission 29 and resonant Auger 30 spectroscopy. With variations of the A ions in lead bromide perovskites, it has been shown in measured and simulated bromine K-edge X-ray absorption spectra that hydrogen bonding strongly influences bromine σ * and π * bands in the conduction band 31 .…”
Section: Introductionmentioning
confidence: 99%
“…With variations of the A ions in lead bromide perovskites, it has been shown in measured and simulated bromine K-edge X-ray absorption spectra that hydrogen bonding strongly influences bromine σ* and π* bands in the conduction band. 31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation